Investments in corporate training of truck drivers in truck fleets: comparative economic assessment of mentoring and standard instruction in the conditions of highway transportation - Pronenko, Ivan (Global Prosperity, 2025)
Abstract. The relevance of the study is based on the task of increasing the economic efficiency of truck fleet operation under conditions of military-economic instability, the transformation of logistics markets, and increasing requirements for long-distance freight traffic safety, where the quality of training of truck drivers directly affects the costs, risks and competitiveness of carriers. The purpose of the article was to provide a comparative economic evaluation of investments in mentoring and standard training as alternative models for the corporate training of drivers of freight truck fleets. The method of research was a set of statistical analyses of indicators of development of transport industry, empirical examination of the level of professional competencies of drivers (n=21) using a four-level evaluation system (59 test questions, 100-point scale), correlational analyses of the dependence of knowledge on intensity of professional experience (R2 = 0.6364; for the most difficult level R2 = 0.83), as well as comparative economic analyses of corporate training methods. The result was that the contribution of the transport industry to GDP of Ukraine decreased from 6.36% in 2014 to 4.05% in 2025; however, the sales volume of services of freight road transport has been growing (in 2015 it has grown in 4.4 times which proves the adaptive ability of the industry and gives the reason to invest into human resources). It was determined the structure dominance of the small-size businesses (96% enterprises that are provide 52% of services), which is critically sensitive to the costs of driver's errors. The testing results revealed high knowledge in the sphere of technical components of truck drivers (63.9%) and low in the segment of real road situations (41.5%); 15 of the 21 respondents were not able to meet the average value threshold of 50% which gives to predict a significant level of errors during real driving of trucks. It was shown the non-linear dynamics of the dependence of knowledge on the level of experience, where with the growth of the latter the average score is reduced by 20-25 points. This proves the necessity of systematized up-to-date driving knowledge. Practical relevance is in providing opportunities of implementing proposed model of corporate mentoring to improve costs and safety of fleet transportation, and to develop professional responsibility culture of drivers.